Survival, graft function, and incidence of allograft vasculopathy in heart transplant patients receiving adverse risk profile donor hearts. Issue 8 (29th July 2018) - Berg, Katrine; Clemmensen, Tor S.; Tram, Else Marie; Koefoed‐Nielsen, Pernille; Ilkjær, Lars B.; Poulsen, Steen H.; Eiskjær, Hans
Abstract: Aim: To clarify if use of adverse cardiovascular risk profile (ARP) grafts is associated with impaired long‐term outcomes after heart transplantation (HTx). Methods: Survival was obtained from Scandia Transplant and a local database. ARP donor inclusion criteria: ≥55 years, diabetes mellitus, arterial hypertension, hypoxemia‐induced death, impaired left ventricular (LV) ejection fraction. ARP donors were compared to donors not meeting the eligibility criteria. Sub‐analyses were made for donor age. Results: In total, 302 HTxs were performed in 296 patients from 31 December 1992 to 11 August 2016. Median survival was 16.5 years (95% CI, 14.3‐22.9), there was no difference between profiles (HR 0.63 (95% CI, 0.33‐1.19), P = 0.15). LV systolic function was significantly better in ARP donors ( P < 0.05). Freedom from cardiac allograft vasculopathy (CAV) was comparable between profiles, HR 0.9 (95% CI 0.5‐1.5). Donor age predisposes to CAV (high to low age: HR 2.8 (95% CI 1.7‐4.5), P < 0.0001). Median survival was comparable in patients receiving allograft ≥55 and <55 years (HR 0.77 (95% CI 0.4‐1.4), P = 0.38). Conclusion: Long‐term survival and graft function were excellent in patients receiving ARP grafts. Older grafts were associated with CAV but did not influence survival. Thus, the strategy of expanding availability using ARP grafts seems safe.